Seguridad y Salud En “Detail Pro”: Identificación y Evaluación De Riesgos (2024)
The research project carried out in the company "Detail Pro" was based on identifying and mitigating the occupational risks that workers face in their daily lives. To achieve this objective, the risk management methodology established in the Colombian Technical Guide GTC 45 was applied.